Physiological Studies of Encystment in Azotobacter vinelandii - Sadoff, H. L. (1971)
Azotobacter vinelandii, in late exponential growth phase, encysts when the glucose in the medium is replaced with β-hydroxybutyrate. A final cell division then occurs without apparent deoxyribonucleic acid (DNA) synthesis, resulting in a reduction from two to one nucleoids per cell and a final DNA content of 3.2 × 10(−14) g per cell. This is also the DNA content per cyst. A β-hydroxybutyrate dehydrogenase is derepressed by the addition of the inducer and is identical to the enzyme in acetate-grown cells in its pH optimum, Michaelis constant for substrate, temperature-activity response, and mobility during electrophoresis in acrylamide gel.